Intravenous anti-VEGF agents with RGD peptide-targeted core cross-linked star (CCS) polymers modified with indocyanine green for imaging and treatment of laser-induced choroidal neovascularization. (1st July 2020) - Cai, Wenting; Chen, Qijing; Shen, Tianyi; Yang, Qian; Hu, Weinan; Zhao, Peng; Yu, Jing
Abstract : S-PEG-ICG-RGD-RBZ NPs were synthesized to intravenously deliver anti-VEGF agents to choroidal neovascularization (CNV) areas for the treatment of CNV. Abstract : Age-related macular degeneration (AMD) is a leading cause of irreversible visual loss among elderly persons, of which wet AMD is characterized by choroidal neovascularization (CNV). We herein developed nanoparticles with good biosafety for effective treatment of choroidal neovascularization (CNV). S-PEG-ICG-RGD-RBZ NPs were synthesized and characterized by ZP, DLS, UV–Vis, TEM and Coomassie Brilliant Blue staining analyses. In our study, the S-PEG-ICG-RGD-RBZ NPs exhibited good biocompatibility in vitro and in vivo . There was no cellular toxicity, dead cells, apoptosis or genotoxicity in the studied concentration range in vitro ; meanwhile, intravenous injection of the designed NPs did not cause histological damage or apoptosis in the organs in vivo, including the heart, liver, spleen, lung, kidneys and brain. The designed NPs inhibited VEGF-induced proliferation, cell migration, tube formation and expression of CD31 and VEGF in vitro . Meanwhile, in vivo studies also indicated the inhibition of CNV development by NPs. What's more, the CNV area was imaged after intravenous injection of NPs modified with indocyanine green. The NPs were mainly targeted to CNV areas and did not remain in the other organs. In summary, S-PEG modified with RGD was designed as a powerful carrier to deliver anti-VEGF agents to CNV areas. The smart NPs, which have good cellular compatibility, hold great potential for drug delivery in CNV treatment.